Cortical blindness after cervical spine surgery in supine position – A rare case report and review of the literature - Mulukutla, Raghav; Yelamarthy, Phani; Vadapalli, RamMohan (Asian Journal of Neurosurgery, 2021)
We report the first case of perioperative visual loss due to cortical blindness after supine cervical spine surgery. A 46-year-old female presented with severe right-sided brachialgia of 1½ years' duration. Her magnetic resonance imaging (MRI) (cervical spine) showed severe right foraminal stenosis at C5–6. She underwent C5–6 anterior cervical discectomy and fusion. Nine hours after surgery, during a routine postoperative round, the patient complained of complete bilateral visual loss. The fundus examination and pupillary light reflex were normal. MRI of the brain showed the posterior cerebral artery infarct with hypoplasia of the left vertebral artery. She was transferred to the neurointensive care unit where antiplatelet treatment was started along with heparin. Her vision slowly began to improve, and at the end of 1 year, she had a reasonable visual acuity in both eyes. It is now standard practice in our institution to check patients' vision immediately after surgery.
Keywords: Cervical; cortical blindness; infarct; perioperative visual loss; spine surgery; supine